EL AUGE DEL NACIONALISMO COMO IDEOLOGÍA POLÍTICA EN EL CONTEXTO DE LA GLOBALIZACIÓN Y LA REGIONALIZACIÓN (Revista Inclusiones, 2019)
The development and dynamics of contemporary international relations creates prerequisites and conditions for manifestation of the varieties of nationalism as a belief, sentiment, duty and behavior on the one hand, and on the other hand – as a reactionary ideology and politics stimulating and evoking feelings and attitude of superiority of one nation over others, or negative feelings between them.